LEARNING MATHEMATICS OF KPK MATERIAL USING STUDENT ASSIGNMENT METHOD GRADE IV - Kalyana M, Dyani (Academic Journal Research, 2025)
Objective: The main objective of this study is to Improve the process of learning mathematics, especially in the main material of KPK Using the Assignment Method for Grade IV Elementary School Students. Method: In teaching mathematics to students, the material should not be delivered abstractly and formally but using the assignment method. In teaching mathematics to students, the material should not be delivered abstractly and formally but using concrete objects around the students. Results: The use of the Assignment Method can be applied to improve the learning of mathematics with the subject matter of KPK through the assignment method for Grade IV elementary school students, this is proven by the students’ learning outcomes who have been able to complete the tasks given by the teacher well, students have mastered mathematics learning about the least common multiple, the learning given by the teacher can be digested and understood by the students, students conduct question and answer sessions with the teacher without any burden. Novelty: One way that teachers do in teaching mathematics to students is to teach by paying attention to the level of students' thinking. In learning mathematics, what teachers should do in teaching mathematics to students is to teach by paying attention to the level of students' thinking.